Denitrification of high strength nitrate bearing acidic waters in granular sludge sequencing batch reactors. (April 2017) - Nancharaiah, Y.V.; Krishna Mohan, T.V.; Satya Sai, P.M.; Venugopalan, V.P.
Abstract: Nitrate containing acidic wastewaters are generated in nuclear fuel cycle operations. These waters are often neutralized prior to either storage or biological treatment. In this study, treatment of high strength nitrate bearing acidic waters was investigated in a sequencing batch reactor. A six liter reactor was inoculated with activated sludge and operated in sequencing batch reactor mode by feeding simulated nitrate wastewater at pH 7.5. After establishing denitrifying microbial consortia in the form of compact granules, the pH of the feed was gradually decreased to 5.0 and then to 4.0. The in situ neutralization of the feed in the reactor by the denitrification-driven alkalinity and the acclimatization strategy helped to achieve complete and stable denitrification during long term operation. The denitrifying microbial community developed in the sequencing batch reactor predominantly consisted of rod- and cocci-shaped microorganisms. This study showed that nitrate bearing acidic effluents can be directly denitrified in granular sludge sequencing batch reactors without a prior treatment. Thus, in situ neutralization and acclimatization strategy can be a potential approach to be considered for treating nitrate contaminated acidic waters. Graphical abstract: Highlights: Granular sludge was cultivated for denitrification of high strength nitrate. Efficient and stable denitrification of 3 g l −1 nitrate at low pH values of 5.0 and 4.0. Denitrification generated alkalinity for in situ neutralization of low pH waters in sequencing batch reactors. Acclimation of microorganisms improved denitrification of acidic nitrate waters.